2017
DOI: 10.1364/oe.25.017021
|View full text |Cite
|
Sign up to set email alerts
|

Light localization and SERS in tip-shaped silicon metasurface

Abstract: Optical properties of two dimensional periodic system of the silicon micro-cones are investigated. The metasurface, composed of the silicon tips, shows enhancement of the local optical field. Finite element computer simulations as well as real experiment reveal anomalous optical response of the dielectric metasurface due to excitation of the dielectric resonances. Various electromagnetic resonances are considered in the dielectric cone. The metal-dielectric resonances, which are excited between metal nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Furthermore, this group also showed that the thickness of the metallic layer (for gold) has an effect on the SERS enhancement [59]. Lastly, other groups also demonstrated SERS enhancements with other shapes of Si nanosystems such as a tip-shaped silicon metasurface coated with gold nanoparticles [67,68], a hybrid Si nanospheroid network ornamented with gold nanospheres [69], silver-coated Si nanopores [70], or Si nanowire arrays coated silver nanoparticles [71,72]. To conclude Section 2, the interests of the metal-coated Si nanosystems are the use of fabrication techniques known as large-surface techniques, and also the plasmonic coupling between the metallic layer/nanoparticles and the semiconducting silicon substrate [38,58,73] in order to potentially improve the Raman enhancement.…”
Section: Sers Performances Of Metal-coated Si Nanosystems For Chemicamentioning
confidence: 85%
“…Furthermore, this group also showed that the thickness of the metallic layer (for gold) has an effect on the SERS enhancement [59]. Lastly, other groups also demonstrated SERS enhancements with other shapes of Si nanosystems such as a tip-shaped silicon metasurface coated with gold nanoparticles [67,68], a hybrid Si nanospheroid network ornamented with gold nanospheres [69], silver-coated Si nanopores [70], or Si nanowire arrays coated silver nanoparticles [71,72]. To conclude Section 2, the interests of the metal-coated Si nanosystems are the use of fabrication techniques known as large-surface techniques, and also the plasmonic coupling between the metallic layer/nanoparticles and the semiconducting silicon substrate [38,58,73] in order to potentially improve the Raman enhancement.…”
Section: Sers Performances Of Metal-coated Si Nanosystems For Chemicamentioning
confidence: 85%
“…EM resonances in a dielectric lamp, whose symmetry is less than spherical symmetry, may have quasi-continuous spectrum (see Ref. [18]). Small clusters of metal particles are considered in [191].…”
Section: Field Enhancement In Dielectric Resonatorsmentioning
confidence: 99%
“…In Ref. [18], Lagarkov et al have studied the light interaction with a tip-shaped metasurfaces composed of silicon cones (see Figure 25).…”
Section: 3d Dielectric Resonators For Surface Field Enhancementmentioning
confidence: 99%
See 2 more Smart Citations